Estimation of salivary nitrate and nitrite levels in different types of tobacco users - A comparative study - Ivin E John; Jayaprasad Anekar; Raj A Chirakara; Krishna S Kumar; Jayalakshmi Baipadavu (Wolters Kluwer Medknow Publications, 2023)
Background: An important public health concern in India is tobacco use. Its use in different forms plays a role in the initiation and progression of oral carcinogenesis. The high-risk population for oral cancer comprises persons with tobacco-related habits. Objectives: This study aimed to determine and compare the levels of nitrate and nitrite in the saliva of different types of tobacco users (betel quid with tobacco chewing, cigarette smoking, gutka chewing) with those of controls. Materials and Methods: The salivary nitrate and nitrite levels in the salivary samples were assessed using the spectrophotometric absorbance method. Results: The present study showed that there were increased levels of salivary nitrate and nitrite in subjects with tobacco-related habits. Conclusions: This shows that there was an increased nitrate burden in the saliva of subjects with habits and hence they had an increased chance for carcinogenesis.